2018
DOI: 10.1111/aab.12423
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance and biochemical responses of maize plants to drought and re‐watering cycles

Abstract: The ability to recover from drought stress after re-watering is an important feature that will enable plants to cope with the predicted increase in episodic drought. The effects of pre-drought and re-watering conditions on leaf spectral properties and their relationships with the biochemical processes that underlie the recovery from pre-drought conditions should be better understood. The reflectance spectra, 10 spectral reflectance indices (SRIs) and biochemical characteristics of maize (Zea mays) leaves were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…The earliest effects were observed in the visible region, where an increase in red reflectance was present two days after the onset of the drought treatment. Increases in red reflectance attributed to changes in pigment content ( Sims and Gamon, 2002 ; Sun et al, 2018 ) were not visible here, instead red reflectance showed a strong correlation with photosynthetic efficiency (Φ PS 2 or F v ′/F m ′) and Ψ, suggesting that other factors, such as light scattering within the leaf and chloroplast positioning, may have impacted red reflectance during the drought treatment. The negative relationship between red reflectance and Ψ did not differ between treatments, implying that the underlying link is the same for developmental and drought-induced changes.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The earliest effects were observed in the visible region, where an increase in red reflectance was present two days after the onset of the drought treatment. Increases in red reflectance attributed to changes in pigment content ( Sims and Gamon, 2002 ; Sun et al, 2018 ) were not visible here, instead red reflectance showed a strong correlation with photosynthetic efficiency (Φ PS 2 or F v ′/F m ′) and Ψ, suggesting that other factors, such as light scattering within the leaf and chloroplast positioning, may have impacted red reflectance during the drought treatment. The negative relationship between red reflectance and Ψ did not differ between treatments, implying that the underlying link is the same for developmental and drought-induced changes.…”
Section: Discussionmentioning
confidence: 64%
“…A vast number of indices created for remote sensing applications are now used in proximal phenotyping studies. NDVI is a very popular index applied in several drought studies ( Kim et al, 2011 ; Römer et al, 2012 ; Behmann et al, 2014 ; Sun et al, 2018 ). Its performance ranges from no drought-induced differences to a significant reduction in NDVI values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This wavelength is often used to measure the pigment concentration in the canopy, the senescence pattern, photosynthetic activity, biomass accumulation, leaf area, the yield of grains, and plant hydration status ( El-Hendawy et al, 2015 ; Gizaw, Garland-Campbell & Carter, 2016 ; Prasad et al, 2009 , 2007 ; Sun et al, 2019 ). Ground-based proximate sensing is a simple, rapid, practical, and cost-effective method for determining the spectral reflectance of the canopy and has been effectively utilized to evaluate a variety of phenotyping features associated with drought resistance ( El-Hendawy et al, 2015 ; Gizaw, Garland-Campbell & Carter, 2016 ; Sun et al, 2018 ; Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report showed that a watering treatment following a drought can lead to a greater recovery of some key functional traits in plants (Harrison et al, 2018). For example, both full and partial recoveries of leaf pigment and nitrogen contents were observed in drought-stressed maize plants following rewatering (Sun et al, 2018). Drought has been an important factor in the growth of maize, the most widely grown crop in the world.…”
Section: Introductionmentioning
confidence: 99%